An Analysis of the Human Resource Features of Political Executives Engaged in Local Self Governance - Abraham, Joseph (Prabandhan: Indian Journal of Management, 2012)
The elected people's representatives wield political power and take policy decisions in the day-to-day functioning of the Panchayati Raj Institutions (PRIs). The statutory functions and powers enjoyed by these local bodies are manifold. The Panchayati Raj Institutions are mandatory organizations for local self-governance given by the 73rd constitution amendment. And to a large extent, the states' departmental bureaucracy is placed at the command and disposal of local governments for planning and executing various developmental tasks. During the last one-decade, the decentralization processes have witnessed revolutionary progress and now are being stabilized in the state of Kerala. To learn from these experiences; the educational attainments, age levels, experience possessed, trainings attained, gender composition, socio-economic status and activity patterns of the elected people's representatives need to be separately analyzed to characterize the emergent human-resource behavior patterns of this relatively new segment of political executives. For analytical purpose, the case of a middle layer, out of the three-tier Panchayati Raj Institution (PRI) set up in Kerala with special reference to Eranakulam district is taken up to highlight the human-resource characteristics of the existent elected political executive functionaries, their knowledge of the programmes and training needs that will help engage them in local self-governance of the Block Panchayats. The leadership of elected people's representatives of local bodies, especially by those of the women members is expected to facilitate better convergence and integration of various women oriented programmes.